Kinetics of Interface Reactions: proceedings of a Workshop on Interface Phenomena, Campobello Island, Canada, September 24-27, 1986 - Grunze, Michael; Kreuzer, H. J. (Springer, 1987)
This book contains the proceedings of a workshop on interface phenomena with special emphasis on kinetics of interface reactions. Each of the three days was devoted to a specific topic of some controversy which was highlighted by invited speakers representing opposing views. The comments of the session chairman summarize the intense discussions and point out directions for further research. More specifically, the first day's discussion centered on "Adsorption-Desorption Kinetics: Dynamics versus Thermodynamics", with invited contributions by D. Menzel and W. Brenig, and a summary by H.J. Kreuzer. The second day was devoted to "Precursors: Myth or Reality?", with major papers by W.H. Weinberg and D. Auerbach. The active discussions were summarized by T. Engel. On the third day, we tried to map out a strategy to study "Kinetics of Phase Transitions at Surfaces", with main contributions by K. Heinz and J.D. Gunton, summarized by P.H. Kleban. An overview and outlook was given on the last day by P. Estrup. In all, the proceedings contain 6 invited lectures, summaries and a dozen contributed papers
Keywords: Konferenzschrift; Kinetik; Oberflächenreaktion